Heat Transfer Enhancement of Circular- and Petal- Shaped Double-Tube-Type Heat Exchangers by Triple Ones - Toshihiko Shakouchi; Kazuma Yamamura; Koichi Tsujimoto; Toshitake Ando (Energies, 2020)
Conventional circular double or triple tube type heat exchanger, DHE or THE, is one of the compact heat exchangers; a large number of studies have been performed to improve their heat transfer performance. The authors demonstrated that a petal-shaped special DHE with a large wet perimeter yields a high heat transfer efficiency, η. In this study, the DHE with six or five petals-, five shallow petals-, and circular-inner tubes were used. To further improve the η of the DHE, a THE with a petal-shaped inner tube along with the middle and outer circular tubes were used. Hot water flowed through the inner tube and cold water flowed through the middle and outer tubes as a counter current flow. The heat transfer was approximately equal; however, the flow resistance (pressure loss) of the outer tube of the DHE could be decreased using the middle and outer tubes under the same amount of cold water as the DHE; consequently, the η could be improved. In addition, the effect of changing the flow path of the hot- and cold-water flows on the η was examined.